2021
DOI: 10.1101/2021.09.06.21262817
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of polygenic risk for suicide attempt and risky behavior on brain structure in young people with familial risk of bipolar disorder

Abstract: Aims: Bipolar Disorder (BD) is associated with a 20-30 fold increased suicide risk compared to the general population. First-degree relatives of BD patients show inflated rates of psychopathology including suicidal behaviors. As reliable biomarkers of suicide attempts (SA) are lacking, we examined associations between suicide-related polygenic risk scores (PRS) - a quantitative index of genomic risk - and variability in brain structures implicated in SA. Methods: Participants (n=206; aged 12-30 years) were un… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 112 publications
0
1
0
Order By: Relevance
“…68 Some evidence suggests that individuals with or at risk for depression are associated with structural alterations in the cuneus. 6971 Previous studies have reported that cuneus gray matter volume is associated with depression 72 and suicidal behavior 73,74 in MDD adults. Kim et al 75 found that MDD adolescents have a thinner cortical thickness in the cuneus.…”
Section: Discussionmentioning
confidence: 99%
“…68 Some evidence suggests that individuals with or at risk for depression are associated with structural alterations in the cuneus. 6971 Previous studies have reported that cuneus gray matter volume is associated with depression 72 and suicidal behavior 73,74 in MDD adults. Kim et al 75 found that MDD adolescents have a thinner cortical thickness in the cuneus.…”
Section: Discussionmentioning
confidence: 99%